2021
DOI: 10.1177/23259671211035780
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graft Bending Angle on Femoral Tunnel Widening After Double-Bundle ACL Reconstruction: Comparison of Transportal and Outside-In Techniques

Abstract: Background: Previous studies have suggested that increased mechanical stress due to acute graft bending angle (GBA) is associated with tunnel widening and graft failure after anterior cruciate ligament (ACL) reconstruction. Few studies have compared the GBA between the outside-in (OI) and the transportal (TP) techniques. Purpose: To evaluate the influence of GBA on clinical outcomes and tunnel widening after ACL reconstruction with OI versus TP technique. Study Design: Cohort study; Level of evidence, 3. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Although a greater GBA was correlated with some of worse patient-reported outcomes in our study, these correlations were too weak to verify that the GBA affects clinical outcomes. In a previous study, Lee et al [ 23 ] also demonstrated that the GBA did not significantly affect the enlargement of bone tunnels and clinical outcomes, regardless of the surgical techniques. However, several other studies found that an acute GBA contributed to the occurrence of tunnel widening, but did not negatively affect the clinical outcomes [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
“…Although a greater GBA was correlated with some of worse patient-reported outcomes in our study, these correlations were too weak to verify that the GBA affects clinical outcomes. In a previous study, Lee et al [ 23 ] also demonstrated that the GBA did not significantly affect the enlargement of bone tunnels and clinical outcomes, regardless of the surgical techniques. However, several other studies found that an acute GBA contributed to the occurrence of tunnel widening, but did not negatively affect the clinical outcomes [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
“…There are differences among the 3 ACLR femoral tunnel preparation techniques (TT, AMP, OI) in terms of the length and obliquity of the femoral tunnel, 2 , 7 , 8 , 9 , 10 the rate of complication, and possibly the clinical outcomes after ACLR 2 , 9 , 11 ( Table 2 ). In spite of these, the choice of femoral tunnel preparation technique is usually a preference of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the OI technique allows posterior placement of the graft with avoidance of posterior wall blowout. 4 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…The graft bending angle plane, in which the centers of the extra‐ and intra‐articular apertures of the femoral tunnel and the center of the intra‐articular aperture of the tibial tunnel are shown together, was selected to measure the bending angle, as described in previous studies (Fig. 2B) [16, 21].…”
Section: Methodsmentioning
confidence: 99%